Human-information interaction and technical communication : concepts and frameworks - Albers, Michael J. (Information Science Reference, 2012)
"This book works to provide practical knowledge based on a sound theoretical foundation for allowing people to engage in a meaningful dialogue as they make decisions with respect to designing that communication"--Provided by publisher
"Premier reference source"--Cover
Keywords: Information technology; Interpersonal communication